Design of Wideband Dual-Polarized Planar Antenna Using Multimode Concept. (30th October 2016) - Yang, Deqiang; Zeng, Huiling; Wen, Yubo; Zou, Meng; Pan, Jin
Abstract : A wideband dual-polarized planar antenna is designed and analyzed by using the theory of characteristic modes (TCM). The eigenvalue, eigencurrent, characteristic pattern, and modal weighting coefficient are analyzed to bring physical insight to this kind of antenna. The results demonstrate that there are two modes resonant in the operating band for each polarization, which have been combined to form a wider frequency band. A bandwidth of 60.2% (1.72–3.2 GHz) for VSWR < 1.5 with high isolation of 32 dB is achieved simultaneously. The size of the radiator structure is 0.33λ 0 × 0.33λ 0 × 0.22λ 0 (λ 0 refers to the center operating frequency).